Optimalisasi Pemanfaatan Sampah Anorganik Sebagai Media Tanam dalam Upaya Penghijauan Pekarangan Rumah: Studi Kasus - Ardiyanti, Vivin; Lestari, Futry Ayu; Sari, Dwi Novita; Silfiani, Humaira (STKIP HARAPAN BIMA, 2025)
The problem of inorganic waste management and limited green space in rural areas are important backgrounds in this study. This study aims to analyze the optimization of the use of inorganic waste as a planting medium in efforts to green the yards of houses among women village officials. The research method used is a qualitative case study design on women village officials who have implemented the use of inorganic waste as a planting medium in the greening program. Data collection techniques were carried out through in-depth interviews with women village officials involved in the greening program, observations of the practice of using inorganic waste as a planting medium, and documentation of visual changes in the yards of houses. Data analysis techniques used descriptive qualitative analysis with the stages of data reduction, data presentation, and drawing conclusions to identify patterns and findings from the program implementation. The results of the study indicate that various types of inorganic waste such as used gallons can be optimized into effective planting media. Interviews revealed that the driving factors for the success of this program include community environmental awareness, the presence of assistance from the village government, and the economic value of reducing the purchase of conventional pots. This study concludes that optimizing the use of inorganic waste as a planting medium is a sustainable approach to greening the yards of houses while addressing waste problems in rural areas.